Michel Foucault’s legacy to Discourse Analysis (Research, Society and Development, 2020)
What are Michel Foucault’s contributions to Discourse Analysis (DA)? Who brought Foucault to the interior of the DA? When and how did it happen? The answers to these three questions serve as basis for the writing of this epistemological-reflective paper. Thus, we will try to analyze, starting from a resumption of the founding texts of the discipline and, in particular, the thesis of Jean-Jacques Courtine - author who articulates the Foucauldian perspective within the DA -, the estate left by the philosopher and who vividly guides countless works registered under this bias of researches in our country today. To conclude, we also present a census of Research Groups in Brazil, registered with CNPq, whose activities follow this theoretical orientation.